Improving Functionality For The Teachers In View Of Implementation Total Quality Management In Universities: Sociological Study Leghars Souhila - الألي الرافع; Leghars, Souhila (Wisdom Journal For Studies & Research, 2021)
The main purpose of this study is to present the thoughts of the modern paradigm on Total quality management and its application in the field of education. This study aims to identify the methods for use Improving functionality for the teachers in view of Implementation Total quality management in Mascara University. This study, which was conducted at the faculty of humanities and social sciences at the University of mascara, It can improve the functionality of teachers Through an Implementation many methods fitness for use for example planning and orientation, technological formation and training and self-evaluation for the teacher.